Young Adults and Sick Leave Length of Mental Illnesses - Beata Gavurova; Miriama Tarhanicova (Frontiers Media S.A., 2022)
ObjectivesThe objective was to explore whether a sick leave length related to mental morbidity differs across different occupational categories.MethodsIn the analysis, registry of sick leaves was analyzed. Provided analysis is focused on the length of sick leaves related to mental diseases caused by substance use or other factors. Dependent variable is the sick leave length, and the independent variables are the categories of disease and occupation. Kruskal-Wallis test, Shapiro-Wilk test, and Brown-Forsythe (B-F) are used.ResultsThere are differences in mental sick leave lengths caused by substance use or other factors. In the case of mental illnesses attributable to drugs, differences in the sick leave duration among different working groups were not found. Considering mental disorders caused by other factors, there are differences in the sick leave duration among different working groups.ConclusionsThere is no evidence of longer sick leave in people diagnosed with mental disorder related to substance use. Differences in occupational categories do not relate to sick leave length.